Comprehensive Sequencing of Environmental RNA From Japanese Medaka at Various Size Fractions and Comparison With Skin Swab RNA - Kyoshiro Hiki; Toshiaki S. Jo (Environmental DNA)
ABSTRACT Environmental RNA (eRNA) is emerging as a non‐invasive tool for assessing the molecular status and physiological responses of macro‐organisms, but key information on its origin and particle sizes remains unclear. In this study, we aimed to determine the optimal filter pore size range for eRNA analysis and evaluate the contribution of skin and mucus to eRNA profiles. We performed comprehensive RNA‐sequencing of eRNA (> 13 Gb/sample) collected from tank water containing Japanese medaka (Oryzias latipes), using sequential filtration through filters with pore sizes of 10, 3, and 0.4 μm. Fish skin and mucus RNA was collected using a cotton swab, then sequenced, and compared with eRNA. Our results showed that the 3–10 μm fraction contained the lowest relative abundance of microbial RNA, the highest amount of medaka eRNA, and the largest number of detected medaka genes (5398 genes), while the 0.4–3 μm fraction had the fewest (972 genes). Only a small number of genes (42 genes) were unique to the 0.4–3 μm fraction. These findings suggest that a 3 μm filter is optimal for eRNA analysis, as it allows for larger filtration volumes while maintaining the relative abundance of macro‐organism eRNA. Furthermore, 81% of the genes detected in eRNA overlapped with skin swab, indicating skin and mucus are major sources of fish eRNA.